2011
DOI: 10.1123/jpah.8.s1.s32
|View full text |Cite
|
Sign up to set email alerts
|

“Just Let Me Play!”—Understanding Constraints That Limit Adolescent Sport Participation

Abstract: The sociodemographic characteristics of middle school students appear to be a significant factor in their perception of constraints to sport participation. Identifying constraints associated with sport participation can enable policy-makers and administrators to be more deliberate in channeling resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 42 publications
(56 reference statements)
4
30
0
Order By: Relevance
“…Therefore, while providing 6th graders with the opportunity to "try-out" for sport teams may increase the number of 6th grade participants, the overall number of students participating in school sports across all grades would likely remain unchanged due to the displacement of current participants. Keeping 6th grade students engaged is critical as prior research has shown that both physical activity and sport participation rates decline around the beginning of middle school [34][35][36]. Thus, increasing opportunities to engage children rather than providing additional barriers should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, while providing 6th graders with the opportunity to "try-out" for sport teams may increase the number of 6th grade participants, the overall number of students participating in school sports across all grades would likely remain unchanged due to the displacement of current participants. Keeping 6th grade students engaged is critical as prior research has shown that both physical activity and sport participation rates decline around the beginning of middle school [34][35][36]. Thus, increasing opportunities to engage children rather than providing additional barriers should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Alexandris and Carroll (1997a) found in a study in Greece in which nonparticipants experienced significantly more intrapersonal constraints than participants. Constraints were experienced most frequently by women, lower educated people, the elderly and people with a minority background, indicating a relationship between the experience of constraints and social class (Alexandris & Carroll, 1997b;Casper, Bocarro, Kanters, & Floyd, 2011;Shores, Scott, & Floyd, 2007). Alexandris, Kouthouris, Funk, and Chatzigianni (2008) stressed the importance of intrapersonal constraints for involvement and loyalty among skiers.…”
Section: Subjective Constraintsmentioning
confidence: 99%
“…The fi ndings of the latent mean diff erences across physically inactive and active participants revealed that physically inactive participants reported higher scores than physically active participants did in all constraints except for accessibility, which are similar with previous fi ndings among young people (e.g., Masmanidis, et al ., 2009 ;Casper, et al ., 2011a ), but diff erent from the fi ndings among adults (e.g., Alexandris & Carroll, 1997b ) between participants and non-participants. However, it is diffi cult to identify the potential reasons for these diff erences or similarities because previous studies failed to exclude the infl uences of the measurement issues on the results.…”
Section: Discussionmentioning
confidence: 94%